Provision of education to increase knowledge in the prevention of diarrhea in children - Ari Setiawati; Andi Suyatni Musyrah; Rusli Rusli (Edukasi Ilmiah Indonesia, 2024)
Introduction: Prevention of diarrhea in children involves various steps that parents or educators can take to improve knowledge and healthy living habits. By providing this education, parents and educators can help increase children's knowledge about diarrhea prevention and form healthy living habits to prevent the disease. Objective: knowing the provision of education to increase knowledge in preventing diarrhea in children. Methods: Experimental queasy with one group pretest-posttest design. The research sample was 60 respondents with consecutive sampling techniques. The instruments in the study were questionnaires and counseling units regarding diarrhea-statistical data analysis using the Wilcoxon Sign Rank Test. Results: Statistical tests show p values of 0.000 < ? 0.05, so it means that there is a significant influence between providing education about diarrhea and the level of knowledge of mothers in preventing diarrhea in children. Conclusion: There is a significant influence between the provision of education about diarrhea and mothers' knowledge level in preventing diarrhea in children. Increasing knowledge about diarrhea prevention in children involves various aspects of hygiene, nutrition, and healthy lifestyle. This holistic approach is expected to reduce the risk of diarrhea in children and improve their overall health. In addition, it is crucial to constantly monitor the child's health, respond quickly to diarrhea symptoms, and seek medical help if needed.